Perception of families of patients with COVID-19 about hospitalization in adult intensive care (Research, Society and Development, 2023)
Objective: To know the perception of family members of COVID-19 hospitalized patients about the period of hospitalization in an Adult Intensive Care Unit. Methodology: Descriptive and qualitative study with adult family members of patients with COVID-19 admitted to an Adult Intensive Care Unit of a tertiary public hospital in Porto Alegre (RS), Brazil. A sheet with sociodemographic data and a semi-structured questionnaire were used. The interviews were conducted between November and December/2020 by phone call and the sample was determined by data saturation. Bardin’s content analysis was used. Results: Nine family members aged between 23 and 56 years old participated. Predominated women, mostly daughters. The number of days in isolation ranged from 8 to 31. Five categories emerged: The Intensive Care Unit as a death sentence; The impact of a new disease; Family distance and exclusion; Support networks; The imminence of death. Conclusion: Hospitalizations due to COVID-19 in Intensive Care Unit were permeated by fear and anguish of family members, increased because it is a new and incurable disease. The need for isolation made physical contact impossible, impacting the understanding of the condition and the elaboration of mourning. The support of team healthcare, other family members and friends, faith and religiosity emerged as protective mechanisms. Anticipatory grief, fear of death without saying goodbye and multiple losses are central to grief. Emotional support for family members is essential, in order to promote psychological well-being and prevent psychological injuries and complicated grief.